دور التقنيات الحديثة في تطواير الموارد البشرية بوزارة الصحة الصحة العمانية - Mohammed Humaid Mohammed Al Alawi (Universiti Sains Islam Malaysia, 2024)
This study aims to know the situation of the human resources polices in the ministry of health in Oman and the possibility of using the modern techni.ues in the department of human resources and to know the individual differentiations between the employees at the department of human resources and the availability of the re.uirements of modern techni.ues which are due to the following variables gender, job and experience. A .uestionnaire has been used as a tool to collect data. The forms were distributed to 55 employees. The return forms were 100%. The descriptive and analytical approach was used to achieve the aims of the study. The findings of the study showed the facilities of the modern techni.ues in the ministry of health department of human resources was weak and medium and the significance rate was 0.403 between the means of the individuals to measure the availability of the modern techni.ues in the department of human resources and its impact on the development of human resources in the Oman ministry of health and all its aspects based on the level of the variable of experience that is there are significant differences at the level of α ˂0.05 and the rate for the experience was 0.464 within the means of the samples in terms of the impact of the modern techni.ues on the development of human resources in the Oman ministry of health and all its aspect according to the level of the experience variable namely that there are significant differences at the level of α˂0.05. Based on the results, the study recommended to the necessity of the development of the human resource department through taken some procedures to do so.